2021
DOI: 10.1186/s40164-021-00227-0
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF1 promotes hepatocellular carcinoma progression via activating PI3K/AKT/mTOR signaling pathway and inducing epithelial-mesenchymal transition

Abstract: Background N6-methyladenosine (m6A) modification, as the most abundant RNA modification, widely participates in the physiological process and is involved in multiple disease progression, especially cancer. YTH N6-methyladenosine RNA binding protein 1 (YTHDF1) is a pivotal m6A “reader” protein, which has been reported in multiple cancers. However, the role and molecular mechanism of YTHDF1 in HCC are still not fully elucidated. Methods Based on vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 49 publications
3
56
0
Order By: Relevance
“…Currently, the main signaling pathways associated with EMT are TGF-β signaling pathway, Wnt signaling pathway and Notch signaling pathway (Kyuno et al, 2021). In the present study, the main signaling pathways involved in the differential genes were Calcium signaling pathway, NOD-like receptor signaling pathway and mTOR signaling pathway, which were also found to affect EMT directly or indirectly in previous studies (Figiel et al, 2019;Hu et al, 2018;Luo et al, 2021). Our study also found that high metastasis of breast cancer is closely related to biological processes such as cell development, cell differentiation, and regulation of ciliary motility, while in low metastasis natural killer cell-mediated immunity, leukotriene biosynthesis process, positive regulation of BMP signaling pathway, leukotriene metabolic process in response to oxygen free radicals, and monocyte differentiation.…”
Section: Discussionsupporting
confidence: 59%
“…Currently, the main signaling pathways associated with EMT are TGF-β signaling pathway, Wnt signaling pathway and Notch signaling pathway (Kyuno et al, 2021). In the present study, the main signaling pathways involved in the differential genes were Calcium signaling pathway, NOD-like receptor signaling pathway and mTOR signaling pathway, which were also found to affect EMT directly or indirectly in previous studies (Figiel et al, 2019;Hu et al, 2018;Luo et al, 2021). Our study also found that high metastasis of breast cancer is closely related to biological processes such as cell development, cell differentiation, and regulation of ciliary motility, while in low metastasis natural killer cell-mediated immunity, leukotriene biosynthesis process, positive regulation of BMP signaling pathway, leukotriene metabolic process in response to oxygen free radicals, and monocyte differentiation.…”
Section: Discussionsupporting
confidence: 59%
“…In fact, PI3K/AKT/mTOR pathway is known to be related with the progression of various cancers (Golob-Schwarzl et al, 2017;Guo et al, 2021). For example, YTHDF1 could promote HCC via activating PI3K/AKT/mTOR pathway and inducing epithelium to mesenchymal transition (Luo et al, 2021). Brucine promoted the apoptosis and suppressed the proliferation of cervical cancer cells by PI3K/AKT/mTOR pathway (Seshadri, 2021).…”
Section: Mgn Treatment Induced the Autophagy In Huh-7 Cell Linementioning
confidence: 99%
“…Other members of these families were found on the contrary to be downregulated in HCC, such as METTL14 [101,102] and ALKBH5 [97,103], and to exert a tumor suppressive function. Alterations of "readers" were also uncovered in HCC, such as the upregulation of YTHDF1, which increases cell proliferation and migration [104][105][106][107]. YTHDF2 s role in liver cancer is still controversial, with some data showing its downregulation and consequential decreased cell proliferation during hypoxia in HCC cells lines [108], while others reported an upregulation of YTHDF2 in HCC correlating with a poor survival [109].…”
Section: A Rna-related Proteinsmentioning
confidence: 99%